Peningkatan Perilaku Asertif Pada Siswa Korban Bullying di SMP Negeri 27 Kota Samarinda - Lidya Sari; Widyatmoko, Wahyu (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
This study aims to improve the assertive behavior of students who are victims of verbal bullying at SMP Negeri 27 Samarinda City through assertive training techniques in group counseling services. The subjects of the study were grade VIII students who were identified as experiencing bullying and had difficulty expressing their feelings, based on the results of AKPD and interviews with BK teachers. The method used was Guidance and Counseling Action Research (PTBK) with a qualitative and quantitative approach. Data collection techniques included assertive scales, observations, interviews, and documentation. The results showed an increase in assertive behavior after assertive training was given, such as the courage to express opinions, defend personal rights, and reject verbal pressure more confidently. Thus, the conclusion in this study is that assertive training has been proven effective in improving assertive behavior and can be used as an alternative intervention in guidance and counseling services